Monitoring of air pollutants sampling, sample preparation and analytical techniques - Forbes, Patricia B. C. (Elsevier, 2015)
Monitoring of Air Pollutants: Sampling, Sample Preparation and Analytical Techniques provides a comprehensive reference on air pollutant monitoring, addressing experimental approaches to sampling and sample preparation, as well as analytical technologies (instrumental methods) which are applicable to a wide range of topics. The book's purpose is to provide an in-depth resource on the monitoring of ambient air pollutants that covers the basic principles, recent developments, and important applications in the field. Current trends and recent advances are discussed, both with respect to analytical techniques and target air pollutants. All aspects of air pollutant monitoring, from sampling, to sample preparation, and analysis, are covered, making this the book of choice for consultation by air monitoring practitioners
Includes bibliographical references and index
Keywords: BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Air / Pollution / Measurement; Environmental monitoring; Wirtschaft; Air -- Pollution -- Measurement; Umweltanalytik; Chemische Analyse; Luftverunreinigender Stoff; Luftverschmutzung; Aufsatzsammlung